Security of information in university eLearning systems - Grzybowski, Rafał (Wydawnictwo Politechniki Łódzkiej, 2011)
The increase in popularity of university eLearning platforms, supporting traditional methods of education, as well as new communication tools development, make the security issues of information stored in these systems becoming increasingly important. The general discussion on security issues in e-learning was inaugurated by M. K. Littman [1] already in 1996. This document has been prepared to identify data security threats existing in a very specific group of computer systems - university eLearning platforms. As a result of the security incidents database analysis and user behavior described in the literature, thirteen security areas have been defined. Activities undertaken in particular areas, described during the data analysis, have a significant impact on at least one of three basic elements of information security.